Fiscal Responsibility in Autonomous Districts: New Profiles of Representation in the Case of the Special Regions of Italy - Buzzacchi, Camilla (European Scientific Journal, ESJ, 2017)
The essay deals with the difficult relationship between fiscal responsibility and representation: it seems that the traditional rule “no taxation without representation” is less and less true, as the responsibility of the representatives, be they those of the national parliament or of the representative bodies of local institutions, is no longer a real guarantee. The case of the Italian system is significant: local taxes have been interpreted in a very singular way by the constitutional case law, as the representatives’ responsibility connected with local government levies is limited to the determining only of certain aspects of the fiscal phenomenon. One first goal is therefore to analyse the atypical fiscal and financial responsibility of local administrators. But a specific phenomenon of the Italian Regions with a special level of autonomy deserves attention. These special Regions have negotiated with the central government a specific regime: since the constitutional implementation process of 2009, they dispose of undeniably high percentages of their territories’ tax revenue. The profiles of derived finance have been eliminated and it has been decided to return to the self-financing model, understood as the prevailing allocation in a fixed share of tax revenues produced within the territory. The case of the special regional revenues of Trentino-Alto Adige is a peculiar one and it is specifically studied in this essay. This work discusses the question of representation regarding tax revenues in a different way, based on a particular type of relation between the wealthproducing context and the institutions.